Analysis of distribution and antibiotic resistance of Gram-positive bacteria isolated from a tertiary-care hospital in southern China: an 8-year retrospective study - Zhang, Xiao; Tan, Liming; Ouyang, Pengwen; Ma, Haiyan; Peng, Jianqiao; Shi, Ting; Xie, Liangyi (Frontiers in Microbiology, 2023)
Objective: Due to the severe drug resistance situation of Gram-negative bacteria, especially Gramnegative enterobacter, relatively little attention has been paid to the changes in Gram-positive bacteria species and drug resistance. Therefore, this study analyzed the prevalence and drug resistance of Gram-positive bacteria in a general tertiary-care hospital from 2014 to 2021, in order to discover the changes in Gram-positive bacteria distribution and drug resistance that cannot be easily identified, inform clinicians in their respective regions when selecting antimicrobial agents, and to provide the basis for the diagnosis of Gram-positive bacterial infection, and for the comprehensive and multi-pronged prevention and control of drug-resistant bacteria. Methods: A retrospective study was conducted on Gram-positive bacteria isolated from patients presented to a general tertiary-care hospital from January 2014 to December 2021. A total of 15217 Gram-positive strains were analyzed. Results: During the 8-year period, the total number and the species of Gram-positive bacteria isolated from clinic increased continuously. The 7 most common species were Streptococcus pneumoniae (21.2%), Staphylococcus aureus (15.9%), Enterococcus faecium (20.6%), Enterococcus faecalis (14.0%), and Staphylococcus epidermidis (7.8%), Staphylococcus haemolyticus (4.8%), Streptococcus agalactiae (3.6%). The isolation rates of Staphylococcus aureus and Streptococcus agalactiae increased, and the isolation rate of Enterococcus faecium decreased. The resistance rates of Staphylococcus aureus to erythromycin, clindamycin, tetracycline, rifampicin and furantoin decreased obviously. The resistance rates of Streptococcus pneumoniae to cefepime (non-meningitis) and ceftriaxone (meningitis) decreased significantly. The resistance rates of Enterococcus faecium to penicillin, ampicillin, erythromycin, levofloxacin, ciprofloxacin and furantoin rose rapidly from 50.3%, 47.6%, 71.5%, 44.9%, 52.3% and 37.5% in 2014 to 93.1%, 91.6%, 84.9%, 86.8%, 86.8%, and 60.0% in 2021, respectively.The total number and the species of Gram-positive bacteria isolated during the eightyear period increased continuously. Streptococcus pneumoniae and Staphylococcus aureus are the main causes of positive bacterial infections in this hospital. The resistance rates of Enterococcus faecium to a variety of commonly used antibiotics increased significantly. Therefore, it is very important to monitor the distribution of bacteria and their resistance to antibiotics to timely evaluate and identify changes in drug resistance that are not easily detected.